Análise da governança plural em franquias agroindustriais: casos de carnes e hortaliças no Centro-Oeste e Sul do Brasil - Rodrigues, Fernanda Chaves (Universidade Federal de São Carlos, 2016)
The Transaction Costs Economics is an important analytical tool in the study of microeconomic organization of firms, especially concerning governance structures adopted by them. Although it is a widespread theory, as the New Institutional Economics as a whole, its empirical application is still incipient in the context of organizational plurality, given that it aims deterministic solutions where transactional attributes align to an optimum governance, which minimizes transaction costs. However, companies often combine alternative forms of governance for the same type of transaction in a given institutional environment, which suggests that the understanding of governance is richer than the choice of alternatives modes of coordination. Therefore, it is extremely desirable the incorporation of plural forms phenomenon to Transaction Costs Economics, so in this research it is proposed, through two case studies, to identify the factors that influence the adoption of plural forms of governance on small size regional franchises from agrifood sector, on structuration and those are suppliers/producers of premiums goods. The choice of franchises as study object due to the fact that these are empirical cases of organizational plurality by excellence, because is usual the concomitant operation of owned and franchisees stores, besides the abundant data about the sector. Moreover, the focus in the agrifood segment is justified by its importance to the Brazilian economy, and mainly by the intrinsic peculiarities of its products – such as perishability and seasonality –, inducing agents to adopt solutions that are faster and more efficient in the management of their businesses. Size, niche market, time and operating range are regularities observed in both cases, similarities that allow comparing them to obtain higher-level theoretical findings, which abstract from the specificities of units analysis. Not only it was listed the reasons why such franchises adopt the organizational plurality, but also this study contributed to the incorporation of plural forms in the analytical scope of traditional Transaction Costs Economics. This research contributed to it in three ways: a) it was evident that the particularities of agrifood chains and products play an important role in the use of organizational plurality in the cases examined; b) the concepts of complexity, strategic behavior and ambiguity proved to be empirically valid and robust at the explanation of the phenomenon of plural forms, and the attributes of transactions contributed to this due to the various interfaces found between them and the other studied constructs; and c) the traditional factors that usually define the optimal hierarchical level in a franchise network, also help to justify why to adopt the organizational plurality in the examined companies, mainly to lead to an increased market power and better strategic positioning of the franchisor front of their franchisees.
Keywords: Transaction Costs EconomicsEconomia dos custos de transação; Formas plurais; Pluralidade organizacional; Franquias; Agronegócio; Plural forms; Organizational plurality; Franchisees; Agribusiness; Agrifood; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO